The study of functional-technological properties of encapsulated vegetable oils - Коротаєва, Євгенія Олександрівна; Неклеса, Ольга Павлівна; Гринченко, Ольга Олексіївна; Пивоваров, Павло Петрович (Eastern-European Journal of Enterprise Technologies, 2015)
Functional-technological properties of encapsulated vegetable oils expand the probability of using the product as a semi-finished product of a high degree of readiness in technologies of culinary products such as leafy vegetable salads, different in pH, sales temperature. Implementation of elastoplastic properties of the product shell ensures the integrity (if necessary) of capsules during mechanical mixing; adhesive properties of the capsule shell provide intactness of the internal oil and fat component, which is effectively practiced in the technologies of extended shelf-life foods. Using sodium alginate and realizing its chemical potential in the technology provides thermostable properties of the shell of encapsulated oil and fat product, which expands the range of new types of fats and culinary products with improved consumer properties and extended shelf life.